Tropical hemato-oncology - Droz, Jean-Pierre; Carme, Bernard; Couppié, Pierre; Nacher, Mathieu; Thiéblemont, Catherine (Springer International Publishing, 2015)
What should you do when you have restricted resources? Written by the most prominent experts from the North and the South countries, this book offers a unique complement to classical hematology and oncology textbooks focusing on specific issues concerning cancers in tropical areas. It presents a thorough review of the specific biological, clinical and therapeutic characteristics of cancers in tropical areas, including their background and epidemiology, public health consequences and transcultural mediation. As such, it will be a valuable resource for all hemato-oncology practitioners, students of oncology or tropical medicine, and other physicians involved in the care of cancer patients who live in tropical countries.